Revisiting the Past: Nostalgic Experience in The Grandmother’s House by Kamala Das - Rashmi Rekha Saikia (The Creative Launcher, 2020)
English poetry written by Indian writers has gained a new momentum by manifesting a new quest of establishing national identity. Kamala Das who took the literary world by storm in the mid sixties emerged as one of the dominant voices in all the leading anthologies of Indo English poetry. My Grandmother’s House, a constituent poem of Kamala Das’ first publication, Summer in Calcutta presents an intriguing sense of nostalgia and uprootedness, It is a forcefully moving poem at war with nostalgia and anguish in sharp contrast with her childhood and her grown up stage. The poet desperately yearns for the return of those days at her ancestral house which was affectionately surprised by her grandmother. The image of the ancestral home stands as a symbol of strong support and pure love that the poet craves for in her loveless married life. Bereft of love in her later life at her husband’s house, Kamala Das yearns to visit the house which one’s was a place of symbolic retreat to a world of purity and happiness. The study attempts to present the nostalgia and the memories the poet ponder in the present about her childhood days.